Evaluasi Penerapan PSAP No. 7 Akuntansi Aset Tetap pada Kantor Dinas Kebudayaan dan Pariwisata Kabupaten Minahasa - Ria Amadita Natasia Palandeng (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2022)
Since the Indonesian government enacted Government Regulation no. 71 of 2010 concerning accrual-based Government Accounting Standards, every financial report of government agencies both at the central and regional levels always refers to the government regulations. This government accounting conceptual framework is implemented in the form of a Government Accounting Standard Statement (PSAP). Fixed assets are one of the important components in supporting the operational activities of government agencies that have duties and functions in accordance with the provisions of the legislation. This study aims to determine the suitability of the application of fixed asset accounting in the Minahasa Regency Culture and Tourism Office based on PSAP No. 07. The analytical method in this research is descriptive qualitative analysis method using data collection techniques in the form of interviews, observations and documentation. The results showed that the application or treatment of PSAP No. 07 of property, plant and equipment related to asset classification, recognition, measurement, valuation, expenditure, depreciation, retirement and disposal, as well as disclosures are in accordance with and comply with the principles of PSAP No. 07 concerning accounting for fixed assets. However, the Minahasa Regency Culture and Tourism Office needs to complete data on fixed assets that are still lacking in the inventory list.